Trees as net sinks for methane (CH4) and nitrous oxide (N2O) in the lowland tropical rain forest on volcanic Réunion Island. Issue 4 (18th November 2020) - Machacova, Katerina; Borak, Libor; Agyei, Thomas; Schindler, Thomas; Soosaar, Kaido; Mander, Ülo; Ah‐Peng, Claudine
Summary: Trees are known to emit methane (CH4 ) and nitrous oxide (N2 O), with tropical wetland trees being considerable CH4 sources. Little is known about CH4 and especially N2 O exchange of trees growing in tropical rain forests under nonflooded conditions. We determined CH4 and N2 O exchange of stems of six dominant tree species, cryptogamic stem covers, soils and volcanic surfaces at the start of the rainy season in a 400‐yr‐old tropical lowland rain forest situated on a basaltic lava flow (Réunion Island). We aimed to understand the unknown role in greenhouse gas fluxes of these atypical tropical rain forests on basaltic lava flows. The stems studied were net sinks for atmospheric CH4 and N2 O, as were cryptogams, which seemed to be co‐responsible for the stem uptake. In contrast with more commonly studied rain forests, the soil and previously unexplored volcanic surfaces consumed CH4 . Their N2 O fluxes were negligible. Greenhouse gas uptake potential by trees and cryptogams constitutes a novel and unique finding, thus showing that plants can serve not only as emitters, but also as consumers of CH4 and N2 O. The volcanic tropical lowland rain forest appears to be an important CH4 sink, as well as a possible N2 O sink.